Are Kansas farms profit maximizers? A stochastic additive error approach. (8th January 2021) - Zereyesus, Yacob Abrehe; Featherstone, Allen M.; Langemeier, Michael R.
Abstract: Profit maximization is widely assumed as a behavioral objective in agricultural economics research. This paper applies deterministic and stochastic tests to examine adherence of a sample of Kansas farms to the profit maximization hypothesis. A modification of Varian's stochastic method is developed to account for farms that have zero netput. Results indicate that none of the farms satisfy the joint hypothesis of profit maximization and nonregressive monotonic technological change under the deterministic case. Results support the existence of nonregressive technological change during the study period for the sample of Kansas farms. Using a rejection criterion of 10% for measurement error in quantity data, most of the sample of Kansas farms (81% based on the additive error model and 92% based on the proportional error model) adheres to joint hypothesis of profit maximization and nonregressive monotonic technological change. The consistency with profit maximization is stronger for those farms that do not enter and exit in the production of an output.